Unravelling determinants of webrooming behaviour- a qualitative inquiry - Cheng, Eugene Xi Aw; Kamal Basha, Norazlyn; Ng, Siew Imm; Ho, Jo Ann (UNIMAS, 2021)
Webrooming, a practice whereby consumers research for products online prior to making their final purchase offline, represents a prevalent form of shopping behavior in the current retailing landscape. This study aims to explore the determinants for and against the adoption of webrooming behavior among Millennials. Semi-structured in-depth interviews were employed to collect data. Data were analyzed through theoretical thematic analysis. Results unveil a number of important themes, categorized based on consumers- (i.e., need for touch, need for interaction, price-comparison orientation, and product knowledge), channel-related factors (i.e., online search convenience, perceived usefulness of online reviews, perceived helpfulness of in-store salespeople, immediate possession, perceived risk), situational factor (i.e., product category), as well as experiential outcome (smart-shopping perception) that arose from webrooming. Considering the limited research on webrooming, this study advances the theoretical understanding on the determinants of webrooming, and offers managerial insight for retailers to deal with this popular shopping phenomenon.